COMPETING ECONOMIC VIEWSREPORT SUMMARY - Th. J. Sargent (Финансы: теория и практика)
Turbulence in the global economy is associated with shocks and risks. As a matter of fact, it is an economic theory that I teach. I spent a significant part of my lifetime trying to understand how the economy, individuals, and the households adapted to the uncertainty risks. The fact that the decision is made now, and the project is implemented in the future, teaches us to think about the prospects. I have to admit that the ideas and approaches that my friends and I have used when examining the economy are largely borrowed from the works of the famous Russian mathematician who laid the foundations of the modern econometrics and macroeconomics, and this is the field of my specialism.I would like to mention a few names that you of course know. They are Pafnuty Chebyshev, a renowned statistician, and Andrey Markov, the inventor of the Markov chain. You can see Markov’s name mentioned on virtually every page in one of my books. There is yet another name, Sotsky. He wrote an amazing article in the 1920s showing how random shocks created a kind of system that formed the business cycles. It changed the modern theory of business cycles completely. I know that the Central Banks in Russia and in other countries rely on this theory. Andrey Kolmogorov and Yuri Rozanov, famous Russian mathematicians, invented the theory of predicting defined processes. Kolmogorov wrote about how one could predict the future in his article written during the WWII.